Construction and Magnetic Study of One‐Dimensional Lanthanide–Radical Chains Involving Pyridinone‐Substituted Nitronyl Nitroxide Radicals. Issue 27 (12th July 2018) - Guo, Jianni; Sun, Juan; Sun, Guifang; Sun, Zan; Li, Licun
Abstract : A new nitronyl nitroxide radical‐containing pyridinone group (NIT‐PhPyO, 1 ) has been synthesized NIT‐PhPyO = 2‐[4‐(4‐pyridinone)phenyl]‐4, 4, 5, 5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide. By using this functionlized nitronyl nitroxide, two isomorphic lanthanide–nitronyl nitroxide radical compounds [Ln(hfac)3 3 (NIT‐PhPyO)2 ] n (Ln = Gd2 and Dy3 ; hfac = hexafluoroacetylacetonate) have been successfully obtained. X‐ray spectroscopic analysis reveals that complexes2 and3 possess a 1D chain structure with Ln2 O2 binuclear units, which represent the first examples of Ln–radical chains involving binuclear Ln2 O2 units. Analysis of the magnetic data indicates that a weak antiferromagnetic coupling exists between two Gd 3+ ions, while the magnetic interaction between the Gd III ion and the coordinated nitroxide group is ferromagnetic. Alternating current (ac) magnetic studies indicate that compound3 displays slow magnetic relaxation behavior at low temperature. Abstract : The first examples of Ln–nitronyl nitroxide radical 1D chains involving binuclear Ln2O2 units have been achieved by using a new nitronyl nitroxide radical with a pyridinone group. Magnetic studies show that the antiferromagnetic interactions dominate the magnetic system. Interestingly, the Dy complex exhibits slow magnetic relaxation behavior.